2008
DOI: 10.1017/s002221510700148x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic approach to juvenile nasopharyngeal angiofibroma: our experience at a tertiary care centre

Abstract: Objective: To evaluate the efficacy of endoscopic exposure and excision for juvenile nasopharyngeal angiofibroma.Design: Prospective analysis of the outcomes of endoscopic removal of the angiofibroma at a tertiary care centre, using endoscopic and radiological parameters.Subjects: Twenty-eight consecutive patients with angiofibroma were included. These patients underwent endonasal endoscopic excision of the lesion, following pre-operative computed tomography and digital subtraction angiography. Post-operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In this respect trigeminal schwannomas and juvenile angiofi bromas should be considered good candidates for these approaches. Preliminary clinical reports [9,10] and also our experience confi rm this possibility. When dealing with malignant neoplasms involving the ITF or the upper parapharyngeal region a wide resection is mandatory, and the choice to treat these kind of patients surgically must be well evaluated.…”
Section: Discussion ▼supporting
confidence: 65%
“…In this respect trigeminal schwannomas and juvenile angiofi bromas should be considered good candidates for these approaches. Preliminary clinical reports [9,10] and also our experience confi rm this possibility. When dealing with malignant neoplasms involving the ITF or the upper parapharyngeal region a wide resection is mandatory, and the choice to treat these kind of patients surgically must be well evaluated.…”
Section: Discussion ▼supporting
confidence: 65%
“…When compared with open resection, they result in significantly less intraoperative blood loss . They do not preclude surgical cure and may allow access to deep structures not fully visualized during open surgery . En bloc resection is not necessary to achieve surgical cure and, by contrast, piecemeal resection can facilitate the approach to difficult anatomic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, endoscopic approaches were used for the management of small (Radkowski stages I and II) tumors . The increase of endoscopic surgical skills together with advances in surgical instrumentation, imaging, and surgical navigation systems enabled, however, the indication of these approaches even for Radkowski stages IIIA and B or University of Pittsburgh Medical Center (UPMC) stages IV and V …”
Section: Introductionmentioning
confidence: 99%
“…There are some authors who found the preoperative embolisation as a risk factor, with a higher rate of JNA recurrence 13,14 . Petruson et al 13 found that the recurrence rate in non-embolized patients was 8% and 41% among embolized patients.…”
Section: Discussionmentioning
confidence: 99%